Molecular and Genetic Basis of Hereditary Connective-Tissue Diseases Accompanied by Frequent Fractures - G. T. Yakhyaeva; L. S. Namazova-Baranova; T. V. Margieva; N. V. Zhurkova; A. A. Pushkov; K. V. Savostyanov (Вопросы современной педиатрии)
Frequent bone fractures in infancy require the elimination of a large number (> 100) of genetic disorders. The modern diagnostic method of hereditary diseases characterized by debilitating course is a new generation sequencing. The article presents the results of molecular-genetic study conducted in 18 patients with clinical symptoms of connective tissue disorders. 10 (56%) patients had mutations in the genes encoding type I collagen chains, leading to the development of osteogenesis imperfecta, 5 (28%) — mutations in IV and V type collagen genes that are responsible for the development of Ehlers-Danlos syndrome. 3 (17%) patients had mutations in the gene encoding fibrillin-1 protein, deficiency of which is manifested by Marfan syndrome. However, the correlation between patient's phenotype and discovered mutations in the investigated gene is established not in all cases.